Clinically meaningful interpretation of pediatric health-related quality of life in sickle cell disease - Beverung, Lauren M. (J Pediatr Hematol Oncol, 2015)
Health-related quality of life (HRQL) measures provide information about disease assessment; however, healthcare providers may be reluctant to use HRQL assessments as scores can be difficult to interpret. We sought to identify levels for impaired pain-related HRQL in children with sickle cell disease (SCD). Children (n=251) completed the PedsQL™ Generic Core Scales and PedsQL™ SCD Module in a multisite study. Using children’s item scores on the Pain and Hurt and Pain Impact scales of the PedsQL™ SCD Module, High, Intermediate, and Low Functioning groups were created. We compared functioning groups to the Pain and Hurt and Pain Impact scale scores to determine levels representing high and low HRQL. These scores were compared to disease severity and the PedsQL™ Generic Core Scales. Scores of 60 or below on the PedsQL™ SCD Pain and Hurt and Pain Impact scales were associated with severe disease and met requirements for impaired functioning on the PedsQL™ Generic Core Scales. Scores of 81 or higher on the Pain and Hurt and the Pain Impact scales can be considered consistent with good HRQL in those domains in SCD. Alternately, scores of 60 or lower are cause for concern and suggest areas of HRQL impairment in SCD.